The Development and Application of High-Efficiency Low-Cost Silicon Thin Film Solar Cell. Issue 1771 (2015) - Tan, Xueshi; Mao, Bingxue; Zhang, Feng; Yang, Jingjing
ABSTRACT: For the industrial application of silicon thin film solar cells, the current focus is on how to realize high-efficiency low-cost production process and minimize light-induced degradation effect, thus effectively reducing the balance-of-system (BOS) costs of system integration. In this paper, a brief introduction based on our development and application in this area is presented, highlighting in the achievement of some layers in a-Si:H/μc-Si:H tandem solar cell by optimizing the property of single layers, such as amorphous intrinsic layer, intermediate reflective layer and microcrystalline intrinsic layer. After transferring the process achievement to the industrial production line, we obtained the low-cost thin-film silicon solar cells with high photovoltaic conversion efficiency of 10.2%.